Effect of temperature and concentration of impurities in the fluid stream on CO2 migration in the Utsira formation. (April 2019) - Hodneland, Erlend; Gasda, Sarah; Kaufmann, Roland; Bekkvik, Tor Christian; Hermanrud, Christian; Midttømme, Kirsti
Highlights: Temperature plays a major role for improved history matching in the Sleipner storage site. Simultaneously accounting for concentrations of impurities and temperature leads to significantly improved comparison with seismic data. Accurate in-situ measurements and simulation of reservoir temperature are valuable knowledge in the planning phase for choice of storage sites. Abstract: A satisfying history match of CO2 plume migration in the Sleipner field of the Utsira formation has been difficult to achieve using multiphase flow simulations. Poor modeling of plume or reservoir temperature and impurities in the CO2 stream have been cited as a source of uncertainty in model predictions. Both of these aspects can have a large impact on the simulation results of plume migration in the Sleipner field where the injected fluid is close to the critical point of CO2 . We have performed multiphase flow simulations in the uppermost sand layer of the Sleipner field (Layer 9) over a range of temperatures and fluid compositions in order to clarify these uncertainties. The results reveal that an increase in temperature by a few degrees and simultaneously accounting for impurities from the separation process lead to significantly improved comparison with seismic data. Between temperature and fluid composition, temperature was the most important predictor for success. The results of this study imply that the impact of temperature on model predictions has previously been underestimated. Implementation of a realistic temperature and fluid composition will lead to better prediction of plume mobility and storage capacity, which is important for screening and planning of optimal storage sites.